Comparing the effectiveness of game literacy education and game coding education in improving problematic internet gaming - Han, Ellie Seunga; Park, YeJi; Yurgelun-Todd, Deborah; Renshaw, Perry F.; Han, Doug Hyun (Frontiers in Psychiatry, 2024)
PObjective Problematic internet gaming by adolescents has been thought to be associated with low self-esteem, depression, anxiety, and attention problems. We hypothesized that both game literacy and coding education would effectively improve problematic internet use. However, game coding education would be more effective in enhancing self-esteem and social anxiety in adolescents than game literacy education. Methods A total of 733 adolescent volunteers were included and randomly assigned to either the game coding education or game literacy education programs. Both programs consisted of eight sessions, each lasting 45 minutes, over four weeks. The coding education sessions included game planning and development lessons and allowed students to create the game's characters, stages, and tutorials directly using Scratch, a free coding program. Game literacy education sessions included lessons on enjoying gaming with a healthy rationale and etiquette. Data on demographics, gaming patterns, and psychological status, including positive/negative perceptions of online games, depression, social anxiety, and self-esteem, were collected. Results Both game coding and game literacy education significantly improved YIAS scores compared to baseline, and there was no significant difference in the YIAS scores between the two groups after the interventions. In the hierarchical logistic regression analysis of all participants, higher YIAS scores, stronger negative perceptions of gaming, and lower attention problem scores at baseline predicted lower levels of internet gaming addiction after interventions. In the hierarchical logistic regression analysis among individuals with game coding education, higher YIAS scores, stronger negative perceptions of gaming, lower attention problem scores, and higher self-esteem scores at baseline predicted lower levels of internet gaming addiction after intervention. In addition, game coding education greatly improved negative perceptions of games, self-esteem, and social anxiety compared to game literacy education. Conclusion Both game literacy and game coding education effectively mitigate internet game addiction. However, game coding education effectively mitigated problematic internet gaming by improving negative perceptions of games, self-esteem, and social anxiety in adolescents. We found that the application of knowledge by students in creating their own games was more effective than simply developing a conceptual understanding of the games.